Students’ Perception of Using E-book to Improve Literacy Skill at the English Education Department of UNISKA Banjarmasin - Devie Dian Nisrina; Bahing Bahing; Indra Perdana (Departement of Mathematics Education, 2023)
This research aimed to explore the students’ perception of using e-book to improve literacy skill. It was quantitative method by using survey design. The sample in this research was the third-semester students at the English Education Department of UNISKA Banjarmasin in the academic year 2022/2023. In collecting the data, the close ended questionnaire was used to explore the students’ perceptions of using e-book to improve literacy skill. There were 20 statements which divided into four indicators, namely: 1) motivation and interest, 2) effectiveness, 3) flexibility, and 4) preferences. It was found that most of the students attained positive perception on the motivation and interest, effectiveness, and preferences. Then, they had very positive perception on the flexibility. Moreover, the overall result of the students’ perception showed that the highest percentage was agreed with 54% and the mean score was 3.98. It can be concluded that most of the students on the third-semester at the English Education Department of UNISKA Banjarmasin in the academic year 2022/2023 agreed and they attained positive perception of using e-book to improve literacy skill.